Osnovne teorijsko-metodološke karakteristike korpusne lingvistike (Philologia, 2021)
This paper reviews the key notions within the corpus lingusitsics approach. Texts are considered to be scientifically observable, quantifiable language units. Corpus is a sample of language. Continuous scales are seen as a possible instrument for the quantification of linguistic data. Context plays a significant role in the identification and descritpion of linguistic units. Reocurrence, co-occurence and frequency are seen as possible evidence for linguistic facts. A patter is a generalized linguistic unit based on this evidence. The idiom principle is seen as primary when denoting strategy and the open choice principle.